Chapter L'Accademia della Crusca e il linguaggio di genere - Marazzini, Claudio (Proceedings e report, 2023)
The article takes stock of the interventions of the Accademia della Crusca on the theme of gender language, retracing the history of the various problems that have emerged over time, and explains the reasons why schwa and asterisk cannot be accepted as recommended solutions.